Home bowel cancer tests and informed choice-is current information sufficient? - K. Howard; G. Salkeld (Elsevier, 2003)
Abstract Objectives: To evaluate the type of information that is available to purchasers of home‐based bowel cancer test kits. Methods: Manufacturers, pharmacies and independent testing programs were contacted to obtain faecal occult blood test (FOBT) kits. State cancer organisations were contacted for information on bowel cancer screening. Information on bowel cancer, the FOBT kit, the testing process and potential benefits and harms of the screening process were assessed using guidelines provided by the UK General Medical Council (GMC). Results: FOBT kits and cancer organisation information provided adequate information on the purpose of screening, the screening process itself and potential benefits, but provided no information concerning uncertainties of screening or potential harms. Conclusions: On the basis of both the UK GMC criteria and patient desires for information, the information available at present falls short of being considered adequate for an informed decision to purchase a home‐based FOBT. Implications: We must ensure adequate and balanced information is available to redress the present information asymmetry to facilitate informed participation in a potentially valuable public health initiative.